1968
DOI: 10.2307/3572593
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Protection of Glycine and Glycylglycine

Abstract: The protective action of a series of organic sulfur compounds and amino acids has been investigated by using glycine and glycylglycine as substrates. A linear relationship is shown to exist between the reciprocal of the G-m value for the substrate in the presence of the protecting agent, and the concentration of this protecting agent. The "protecting activity" of the agents, expressed as the ratio of the rate constants for the reaction of radicals with the protecting agent and the substrate, is determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1990
1990

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Detailed examination demonstrated that the amount of glycine derived from irradiated alanine was too small to explain the phenomenon observed), it is postulated that some interaction between two amino acids including radicals causes the selective decomposition. In previous publication, it was shown that the addition of glycine caused an increase in the radiation sensitivity of tyrosine (Fletcher and Okada, 1961), and that alanine could protect glycine and glycyl-glycine from radiation decomposition (Wheeler et al, 1968), though these effects were attributed to the competitive reactions between different amino acids and mainly hydroxyl radicals. However, our finding indicating that the phenomenon was observed even in the concentrated amino acid solution where the direct action of radiation is considered to be a dominant factor for the radiation damages supports, not the radical competition mechanism, but a kind of direct molecular-molecular interation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed examination demonstrated that the amount of glycine derived from irradiated alanine was too small to explain the phenomenon observed), it is postulated that some interaction between two amino acids including radicals causes the selective decomposition. In previous publication, it was shown that the addition of glycine caused an increase in the radiation sensitivity of tyrosine (Fletcher and Okada, 1961), and that alanine could protect glycine and glycyl-glycine from radiation decomposition (Wheeler et al, 1968), though these effects were attributed to the competitive reactions between different amino acids and mainly hydroxyl radicals. However, our finding indicating that the phenomenon was observed even in the concentrated amino acid solution where the direct action of radiation is considered to be a dominant factor for the radiation damages supports, not the radical competition mechanism, but a kind of direct molecular-molecular interation mechanism.…”
Section: Discussionmentioning
confidence: 99%